2014
DOI: 10.1021/nn405267r
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Vapor Formation of Water at the Solid/Water Interface to Colloidal Solutions Using Optically Excited Gold Nanostructures

Abstract: The phase transformation properties of liquid water to vapor is characterized by optical excitation of the lithographically fabricated single gold nanowrenches and contrasted to the phase transformation properties of gold nanoparticles located and optically excited in a bulk solution system [two and three dimensions]. The 532 nm continuous wave excitation of a single gold nanowrench results in superheating of the water to the spinodal decomposition temperature of 580 ± 20 K with bubble formation below the spin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
71
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(74 citation statements)
references
References 21 publications
2
71
1
Order By: Relevance
“…(6) It has been suggested that collective thermal effects are important in explaining the response of such systems. (7)(8)(9)(10)(11) Here we show, however, that collective thermal effects alone are not sufficient to explain the thermal response of these systems. Rather, light trapping by solutions of particles that simultaneously absorb and scatter light results in highly localized heating, an unanticipated effect that, when combined with classical heat transfer, provides an accurate theoretical description of the system.…”
mentioning
confidence: 54%
“…(6) It has been suggested that collective thermal effects are important in explaining the response of such systems. (7)(8)(9)(10)(11) Here we show, however, that collective thermal effects alone are not sufficient to explain the thermal response of these systems. Rather, light trapping by solutions of particles that simultaneously absorb and scatter light results in highly localized heating, an unanticipated effect that, when combined with classical heat transfer, provides an accurate theoretical description of the system.…”
mentioning
confidence: 54%
“…However, there is no evidence to support the claim that steam production was caused by nanobubbles, i.e., bubbles were formed on top of heated nanoparticles. It should be noted that the solar intensity employed here was 220 Suns, as a few previous work [17,[37][38][39][40][41] has suggested that nanobubbles were unlikely to be generated under relatively low heat fluxes. For example, both Kotaidis et al [42] and Keblinski et al [43] pointed out that a laser power density equivalent to more than Suns was required to form nanobubbles.…”
Section: Steam Generation Mechanismsmentioning
confidence: 99%
“…20 Owing to the technological relevance of these microbubbles, the dynamics of their growth and shrinkage has been scrutinized in several investigations. 7,9,12,[22][23][24][25][26] Plasmonic bubble generation is a complex phenomenon, which involves numerous physical processes, such as heat transfer from the nanoparticle to the liquid, supersaturation of the liquid, phase transitions, bubble nucleation, diffusion of gas dissolved in the liquid, evaporation of the liquid and many others. The irradiation of metal nanoparticles immersed in liquid with a continuous laser at resonant wavelength results in plasmonic excitation of the nanoparticles and thereby, in a rapid increase of the temperature of the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%